2022
DOI: 10.1155/2022/9714591
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Big Data Analysis of Benign Interaction of Great Power Relations and New International Relations Based on Deep Learning

Abstract: The development of a new type of international relations is the advancement and improvement of diplomatic thinking among contemporary nations. It also serves as a crucial yardstick for assessing the future global pattern and the direction of order changes. Proper interaction between major powers can foster the growth of new international relations and has a significant impact on advancing global cooperation and the promotion of human peace. The goal of this essay is to examine how friendly interactions between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, the new type of international relations should be built on the basis of sovereign equality, with mutual respect among countries more prominent. The new type of international relations focuses on transforming the friendly relations between states from form to substance, and emphasizes the contributions and innovations made by each country to the establishment of international relations [2].…”
Section: Sovereign Differencesmentioning
confidence: 99%
“…Therefore, the new type of international relations should be built on the basis of sovereign equality, with mutual respect among countries more prominent. The new type of international relations focuses on transforming the friendly relations between states from form to substance, and emphasizes the contributions and innovations made by each country to the establishment of international relations [2].…”
Section: Sovereign Differencesmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%